(De)coloniality and the radical black tradition in Brazil: a possible dialogue? (Tempo e Argumento, 2025)
The particular social formations of Latin American present differences and similarities in the racialization process of subaltern groups, whether indigenous, black or non-white. These social classification phenomena based on the idea of race, in colonized societies, were theorized by diverse intellectuals in the subcontinent, whether linked to left-wing militancy, social movements and decolonial epistemologies. The possible inferences between the concepts of Coloniality of Power of Aníbal Quijano and the elaborations about Structural Racism, a perspective developed in racial studies in the United States which finds similarities with the brazilian case, among the ideas and theories shown in the black activism of Clóvis Moura and Lélia Gonzalez. Without evidence of a concrete dialogue, the convergence between these theories is, hypothetically, part of the historical-structural methodology, reflecting the close relation between coloniality and raciality with the arising of capitalism and modernity. This conceptual net strengthens the construction of an integrated knowledge and a fruitful dialogue with Latin American critical theory and the Brazilian radical black tradition.
Keywords: coloniality; raciality; Radical Black Tradition